2009
DOI: 10.1038/nature08118
|View full text |Cite
|
Sign up to set email alerts
|

CD14 regulates the dendritic cell life cycle after LPS exposure through NFAT activation

Abstract: Toll-like receptors (TLRs) are the best characterized pattern recognition receptors. Individual TLRs recruit diverse combinations of adaptor proteins, triggering signal transduction pathways and leading to the activation of various transcription factors, including nuclear factor kappaB, activation protein 1 and interferon regulatory factors. Interleukin-2 is one of the molecules produced by mouse dendritic cells after stimulation by different pattern recognition receptor agonists. By analogy with the events af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
314
0
6

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 289 publications
(335 citation statements)
references
References 33 publications
15
314
0
6
Order By: Relevance
“…Here, we show that TLR4‐specific ultrapure (up)LPS‐primed phenotypically activated BMDC, rather than worsening the severity of EAU, significantly prevent the development of EAU. We show that upLPS‐primed BMDC are endotoxin homotolerant (ET‐BMDC) and further show that they are heterotolerant to M. tuberculosis protein extract in that they are (i) susceptible to apoptosis45, 46, 47 (confirmed here) through a CD14/nuclear factor of activated T cells (NFATc)‐associated mechanism, and (ii) fail to secrete IL‐1 β on exposure to M. tuberculosis extract. As M. tuberculosis mediated C‐type lectin receptor signalling via the Syk/CARD‐9 complex,48 a major route for inflammasome activation, has been shown to be an essential mediator of IRBP‐CFA‐induced EAU,48, 49 we propose that inhibition of IL‐1 β secretion is one mechanism whereby heterotolerant LPS‐primed BMDC promote immunological tolerance.…”
Section: Introductionsupporting
confidence: 55%
See 2 more Smart Citations
“…Here, we show that TLR4‐specific ultrapure (up)LPS‐primed phenotypically activated BMDC, rather than worsening the severity of EAU, significantly prevent the development of EAU. We show that upLPS‐primed BMDC are endotoxin homotolerant (ET‐BMDC) and further show that they are heterotolerant to M. tuberculosis protein extract in that they are (i) susceptible to apoptosis45, 46, 47 (confirmed here) through a CD14/nuclear factor of activated T cells (NFATc)‐associated mechanism, and (ii) fail to secrete IL‐1 β on exposure to M. tuberculosis extract. As M. tuberculosis mediated C‐type lectin receptor signalling via the Syk/CARD‐9 complex,48 a major route for inflammasome activation, has been shown to be an essential mediator of IRBP‐CFA‐induced EAU,48, 49 we propose that inhibition of IL‐1 β secretion is one mechanism whereby heterotolerant LPS‐primed BMDC promote immunological tolerance.…”
Section: Introductionsupporting
confidence: 55%
“…Zanoni et al 30, 47, 77. have shown that LPS‐primed BMDC are programmed for apoptosis, unlike LPS‐primed macrophages which, although refractory to a second challenge of LPS, survive in culture for prolonged periods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Macrophages develop from hematopoietic stem cells through common myeloid progenitors in the BM, and repopulate in peripheral tissues [2]. Currently, macrophages can be classified into several different subtypes, based on their reactions to different stimuli [3][4][5]. Macrophages involved in inflammatory responses to bacterial and viral infection are called M1 macrophages.…”
Section: Conflict Ofmentioning
confidence: 99%
“…Regardless of classification controversies about cells of the myelomonocytic lineage, an example of their functional peculiarities is the non-overlapping responsiveness of macrophages and DCs to the prototypical toll-like receptor 4 (TLR4) stimulator lipopolysaccharide (LPS), with features that can only be partially explained by differences in the expression of responder proteins [3]. Adding complexity to the picture is the action of tissue-specific microenvironmental cues, which likely control specialized behaviors and fine-tune cellular identities, in fact representing developmental modifiers operating on differentiated cells [4].…”
mentioning
confidence: 99%